THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) IN INDONESIA: A LITERATURE STUDY - Molina; Muhammad Nur; Erwin Indriyanto; Kumba Digdowiseiso; Zalailah Salleh (RADJA PUBLIKA, 2023)
The incorporation of Corporate Social Responsibility (CSR) in Indonesia has emerged as a significantly crucial matter in the realms of business and sustainable development. This encompasses an understanding of the obligations that corporations have towards society and the environment, as well as the influence of government regulations and the growing concerns of society regarding social and environmental matters. The objective of this study is to analyze the progress of CSR implementation in Indonesia using a systematic literature review. The methodology employed in this study is a Systematic Literature Review, wherein we gather diverse literature sources encompassing the implementation of CSR in Indonesia. The findings indicate that the adoption of CSR in Indonesia has witnessed a favorable expansion, as companies are progressively recognizing the significance of their impact on society and the surrounding ecosystem. During the discussion, we emphasize the significance of government involvement, community engagement, consumer demands, and company awareness in promoting the development of CSR. Non-governmental organizations (NGOs) also have a significant impact in promoting corporate responsibility. Ultimately, CSR plays a crucial role in Indonesia by actively promoting sustainable development and enhancing the well-being of the community. It is an essential component of the company's existing business strategy. This encouraging progress demonstrates a recognition of the significance of corporate social responsibility in attaining sustainable development objectives